Treatment of idiopathic sudden sensorineural hearing loss in diabetic patients by oral prednisolone - Khalefa, Khaled M. Mokbel (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Background: Ideopathic sudden sensorineural hearing loss should be treated urgently without delay by steroid therapy. The study purpose was to determine the efficacy of oral steroids in treatment of ISSNHL in patients with diabetes mellitus. Methods: Prospective cohort study of diabetic patients with ISSNHL to evaluate the effectiveness of oral prednisolone in improvement of hearing. It included 30 patients aged 40-65 years that fulfilled the inclusion criteria. Oral prednisolone 1mg/kg was administered for 2 weeks. Hearing was assessed pre and post treatment by measuring the pure tune average in the form of mean and standard deviation. Blood sugar was monitored by a glucometer. Results: 12 diabetic females and 18 diabetic males were enrolled in this study. There was highly significant improvement in the post treatment pure tune averages at all frequencies without any recorded side effects or complications. Conclusions: Oral Prednisolone was highly efficient in rapid improvement of hearing in cases of ISSNHL in patients with diabetes mellitus with no need for intratympanic steroid injection in any patient. There was not reported any side effects or complications.